Drug induced methemoglobinemia: a case report - Dalal, Shrushti Y.; Dalal, Prateek V. (International Journal of Research in Medical Sciences, 2022)
Methemoglobinemia (MetHb) is an uncommon cause of central cyanosis and hence, not frequently considered in the differential diagnosis. Methemoglobin is an abnormal form of hemoglobin which is produced physiologically due to autooxidation. If this process of autooxidation is disturbed, either due to genetic or due to exogeneous drugs/toxins, its level rises in blood leading to tissue hypoxia. It causes central cyanosis when its level exceeds 3%. We present the case of a 19-year-old male patient who was diagnosed with methemoglobinemia due to the use of dapsone for acne vulgaris. Our case emphasizes the significance of detailed history taking, knowledge and high index of suspicion for drug-induced methemoglobinemia.